Microwave-assisted sample preparation for trace element determination - Flores, Érico Marlon Moraes (Elsevier, 2014)
Microwave-Assisted Sample Preparation for Trace Element Analysis describes the principles, equipment, and applications involved in sample preparation with microwaves for trace element analysis. The book covers well-established applications as well as new trends in this field. Hot topics such as sample preparation for speciation, metabolomics, and halogen determination, as well as the alternatives of sample preparation for special samples (for example, carbon nanotubes, polymers, petroleum products), are also discussed. The use of microwaves in sample preparation has increased in recent decades. Several applications of microwaves for sample preparation can be found in the literature for practically all types of sample matrices, especially for the determination of trace elements by atomic spectrometric techniques, safely and cleanly reducing the time involved in this step. Microwave-assisted sample preparation is not only a tool for research but also for routine analysis laboratories; the state-of-the-art in sample preparation in trace element analysis. This book is the only resource for chemists specifically focused on this topic.--Provided by publisher.